Fantastic Mr. fox = Yaman Tilki - Anderson, Wes; Dahl, Roald, 1916-1990.; Twentieth Century Fox Animation (Twentieth Century Fox, 2009)
An urbane fox cannot resist returning to his farm raiding ways and then must help his community survive the farmers' retaliation.
Based on the novel by Roald Dahl.
Voices : George Clooney, Meryl Streep, Jason Schwartzman, Bill Murray, Owen wilson.
3-6.
Language : Turkish, English, French, Norwegian, Brazilian, Portuguese, Latin spanish, Czech, Thai.
Menu : English, French, Dutch, Brazilian, Portuguese, Latin Spanish, Korean.
Subtitle : Turkish, English, French, Latin spanish, Portuguese, Danish, Finnish, Dutch, Norwegian, Swedish, Czech, Greek, Korean, Thai.
Keywords: Movie -- animated films; Movie -- Based on novel